Implikasi Humor dan Kepuasan Karyawan Terhadap Kinerja UMKM di Indonesia: Studi Literatur - Akh Jalal; Helmi Buyung Aulia Safrizal (BADAN PENERBIT STIEPARI PRESS, 2023)
This study aims to describe the implications of humor interaction and employee satisfaction on the performance of MSMEs in Indonesia. The method used in this research is literature study, which examines research problems with data sources derived from previous studies, books, and other literary sources. This study obtained results in the form of several positive and negative implications of the interaction of humor and employee satisfaction on the performance of MSMEs in Indonesia. These implications form the basis for formulating strategies to improve MSME performance through improvements to humor interactions and increased employee satisfaction. This research is expected to be a guide in improving the work environment to reduce physical and mental pressure at work, so as to maximize performance for the development of MSMEs.